2019
DOI: 10.1002/pssb.201900070
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Intrinsic Direct Band Gap of Janus Group‐III Chalcogenide Monolayers

Abstract: InSe based Janus structures has been investigated. The obtained results 6 suggest that the In 2 SeTe Janus structure has an intrinsic direct band gap 7 which is beneficial for optoelectronic applications. The direct band gap nature 8 of In 2 SeTe Janus structure is due to the strong coupling of p z orbitals 9 between the Se and Te sublayers, which emphasizes the importance of the 10 intra-layer interactions. In addition, the effective mass of the holes in In 2 SeTe 11 is one order of magnitude smaller than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…It shows that the spin-up and spin-down states are well separated, and the Fe spin-down orbitals have negligible hybridization with InSe in valence bands. The VBM of InSe are mainly constructed by the In and Se p z orbitals, which agrees very well with previous reports [ 48 , 49 ]. From Figure 4 , we see that tha I atom is antiferromagnetically coupled with the Fe atom.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It shows that the spin-up and spin-down states are well separated, and the Fe spin-down orbitals have negligible hybridization with InSe in valence bands. The VBM of InSe are mainly constructed by the In and Se p z orbitals, which agrees very well with previous reports [ 48 , 49 ]. From Figure 4 , we see that tha I atom is antiferromagnetically coupled with the Fe atom.…”
Section: Resultssupporting
confidence: 92%
“…However, there is no band splitting at VBM and the maxima of the sombrero top are degenerated (<2 meV). This sombrero shape band feature is largely originated from the Se p z orbitals [ 48 , 49 ]. Since the Se2 is very close to the I1 atom, the interaction between them will have a stronger effect on the band features.…”
Section: Resultsmentioning
confidence: 99%
“…Excited by the successes in studies of Janus dichalcogenides, Janus monochalcogenides structures, especially Janus structures based on group III-VI compounds, have gained attention recently. 11,18 Wan and co-workers indicated that the Janus In 2 -SeTe exhibits higher carrier mobility that of InSe. 19 Also, strain engineering is one of the good ways to modulate the thermal conductivity of InSe-based Janus.…”
Section: Introductionmentioning
confidence: 99%
“…Group III 2 ‐VI 3 monolayers are also proved to be promising photocatalysts for overall water‐splitting with high theoretical solar‐to‐hydrogen efficiency 6. Another class of 2D pS is Janus group‐III chalcogenides (M 2 XY, M = Al, Ga, In; X ≠ Y = S, Se, Te) 18. The Janus M 2 XY monolayers were demonstrated as candidates for nano‐optoelectronics and photocatalytic water splitting 19–23.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Another class of 2D pS is Janus group-III chalcogenides (M 2 XY, M = Al, Ga, In; X ≠ Y = S, Se, Te). [18] The Janus M 2 XY monolayers were demonstrated as candidates for nano-optoelectronics and photocatalytic water splitting. [19][20][21][22][23] The third class of 2D pS is Janus transition metal dichalcogenides (TMDs).…”
mentioning
confidence: 99%